The social capital and cash holdings in an emerging economy - Saeid Homayoun; Maryam Seifzadeh (Economies, 2022)
The present study aims to evaluate the relationship between social capital and cash holdings in firms. The population under study comprises all listed companies on the Tehran Stock Exchange. A total of 175 firms (1050 year-firm) were selected from 2014 to 2020 to evaluate the relationship between variables using the systematic elimination method. Moreover, the moderating role of financial reporting quality in the relationship between social capital and cash holdings was also studied. This paper used multivariable linear regression (panel data) and the EViews software to implement the study's objectives. The present study results show a negative relationship between the social capital of firms and cash holdings and a positive association between social capital and financial reporting quality. In other words, cash holdings drop with the increase in social capital. Further, financial reporting quality improves with the increase in social capital. The financial reporting quality moderates the relationship between the social capital of firms and cash holdings. This paper indicates that the region's social capital, where the firm is located, has a significant role in contributing to its cash value. The current study is the first to assess social capital structure in the cash holdings literature. The impacts of social capital contribute to financial outputs. Social capital has a positive economic result against strong cooperation norms and dense social networks. Few studies analyzed the effect of social capital on firms' decision making. In this area, the present study contributes to the literature development and the impact of social capital on firms' results.
Keywords: 330; cash holdings; corporate governance; emerging markets; financial reporting quality; social capital